Antisperm antibodies in repeat‐breeding cows: Frequency, detection and validation of threshold levels employing sperm immobilization, sperm agglutination and immunoperoxidase assay. (8th December 2016) - Srivastava, SK; Shinde, S; Singh, SK; Mehrotra, S; Verma, MR; Singh, AK; Nandi, S; Srivastava, N; Singh, SK; Goswami, TK; Bhure, SK; Kumar, H; et al.
Contents: Antisperm antibodies have been found in repeat‐breeding(RB) cows, and those causing agglutination and/or immobilization of sperm are considered to be closely related to unexplained infertility. However, a standard protocol for identifying antisperm antibodies (ASA) in cattle is not validated. Therefore, an investigation was undertaken to evaluate sperm immobilization (SIT), sperm agglutination (SAT) and immunoperoxidase (IPT)assays for detection of ASA in serum and their respective threshold levels for confirmation. Animals (heifers, normally breeding, repeat‐breeding and pregnant animals) that were free from IBR, brucellosis and uterine infections (screened by clinical examination) were included in the study. Sperm agglutinating, sperm immobilizing and antisperm antibodies evaluated by respective assay were significantly higher ( p  <   .05) in RB cows compared to other groups. The SIT assay was able to identify 61% of RB caused by ASA, more than those employing SAT and IPT. Furthermore, a dilution rate of 1:5 and 1:80 (confirms 59.0 and 57.0% RB+ve)were sufficient to diagnose ASA by SAT and IPT, respectively. Results indicate the presence of __12.6% clumped spermatozoa and __ 2.6%(cut‐off value) peroxidase‐positive spermatozoa at 1:5 and 1:80 dilutions diagnosed with SAT and IPT, respectively, may be considered as repeaters arising out of ASA. Furthermore, study also showed the presence of lower incidence of ASA positivity in other groups of animals (heifer<normal breeder<pregnant animals) compared to repeaters. Study results show that although IPT is more specific and accurate but SAT and SIT are comparatively simple and cost‐effective assays suitable for detecting ASA under field conditions and thus can be recommended for screening of repeaters.